Karakteristik Pendidik Dan Peserta Didik Dalam Al-Qur'an Surah Al-Fatihah - Supriyanto, Asep (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Surah Al-Fatihah as the opening chapter in the Qur'an contains profound educational values, both for educators and students. This article aims to examine the ideal characteristics of educators and students as implied in the content of Surah Al-Fatihah. By using a thematic approach (maudhū'ī) and the bil-ma'tsur and bil-ra'yi interpretation methods, this discussion shows that Al-Fatihah provides a foundation for spiritual, moral, and intellectual character in the educational relationship between educators and students. The results of the study show that Surah Al-Fatihah is not only a prayer, but also a basic principle of character formation in the process of Islamic education